Bubble-mediated methane release from polluted Dalian Bay in China in summer, 2016. (1st September 2019) - Kunpeng, Zang; Nan, Zheng; Xuemei, Xu; Lingxi, Zhou; Juying, Wang
Abstract: Bubble-mediated methane (CH4 ) released from the highly polluted Dalian Bay in China and its effect on the distribution of atmospheric CH4 were observed in summer of 2016. The determined components in bubble sample included CH4, carbon dioxide (CO2 ), nitrous oxide (N2 O) and water vapor, etc. Tidal movement was the dominant factor regarding the bubble release rate. The mole fraction of CH4 in the bubbles reached 0.378 mol mol −1, resulting in an ejective flux of 73.52 mmol m −2 d −1, which was 14.8 times of diffusive flux, and probably induce a direct effects on the horizontal and vertical mole fraction distribution of local atmospheric CH4 . Thus, bubble-mediated CH4 release from polluted coastal seas is a hot-spot for CH4 emissions, and predominantly caused by long-term human activities. Highlights: Components in bubbles released from the highly polluted Dalian Bay included CH4, CO2, N2 O, and water vapor, etc. The dominant factor affecting the bubble release rate was tidal movements in summer. The mole fraction of CH4 in bubbles reached 0.378 mol mol −1 . The sea-to-air CH4 flux of bubble ebullition was 14.8 times of diffusive flux. The distribution of CH4 in boundary air could be influenced directly by bubble-mediated CH4 .